What happens at night a novel - Cameron, Peter 1959- (Catapult, 2020)
"An unnamed American couple travels to a strange, snowy European city to adopt a baby. It's a difficult journey that leaves the wife, who is struggling with cancer, desperately weak, and her husband worries that her illness will prevent the orphanage from releasing their child. On arrival, the couple checks into the cavernous and eerily deserted Borgarfjaroasysla Grand Imperial Hotel where the bar is always open and the lobby populated with an enigmatic cast of characters ranging from an ancient, flamboyant chanteuse to a debauched businessman to an enigmatic faith healer. Nothing is as it seems in this baffling, frozen world, and the more the couple struggles to claim their baby, the less they seem to know about their marriage, themselves, and life itself."
Keywords: Americans / Europe / Fiction; Adoption / Fiction; Cancer / Patients / Fiction; Domestic fiction; Fiction